The Effect of Hydrothermal Duration on the Formation of Activated Edgesites of 2-H Molybdenum Disulfide and the of Hydrogen Evolution Performances of the Material - Premadasa, P.M.; Panamaldeniya, S. A.; Munasinghe, H.; Gunawardhana, N. (University of Jaffna, 2023)
Molybdenum disulfide (MoS2) is a nontoxic, environmentally friendly, abundant semiconducting material which is widely used in the areas of hydrogen storage, gas sensing and, solid super lubricant. It has three major phases called 1-T MoS2, 2-H MoS2 and 3-R MoS2. Among them 2-H MoS2 form is the stable form which has a hexagonal phase structure with an activated edge. Therefore, Activation of the material is possibly changing by making differences on nature of material edges. In this work, we report that influence of duration of hydrothermal process toward the growth of edge sites of 2-H molybdenum disulfide nanocomposites. In this study, we have synthesized three 2-H MoS2 nanostructures by facile hydrothermal route by using Ammonium molybdate, Thioacetamide, and urea as the basic precursors. All the samples were prepared at 200 ℃ temperature by changing the duration of hydrothermal process as 24h, 36h and, 48h. The samples were characterized by powder X-ray diffraction (PXRD) and Scanning electron microscope (SEM) for the phase confirmation and morphological characterizations respectively. Next, Electrochemical characterizations were carried out by using linear sweep voltammetry under the basic medium. Powder X-ray diffraction results confirmed that the prepared three products were at the Hexagonal phase of MoS2 with minor level of impurity. The SEM images show that the as-prepared structures have a Plate-like structure with sharped edges. Then the Linear sweep voltammetry of the materials verified that the high number of sharped edges of MoS2 nanocomposites leads to excellent activity for Hydrogen evaluation reaction (HER). When compared to others, 48 h material has a higher number of sharped edge sites and the best performances in HER. Finally, the sharpness and amounts of edge sites are possible to control with the duration of hydrothermal process and 2-H MoS2 with more number of sharped edge sites were found to increase the performances of HER
Keywords: Edge sites; Global warming; Hhydrothermal synthesis; Hydrogen Evolution; Molybdenum disulfide